Refocusing Public Participation for a New Management Era in Kenya: Insights from Literature - Lokaimoe, Patrick L.; Bartocho, Evaerlyn; Omillo, Francis O.; Omillo, Francis O. (African Journal of Education,Science and Technology (AJEST), 2021)
This study was about a new model of public participation in the wake of globalization, democratization and technological advancement. The model gave ordinary people opportunity to meaningfully contribute to matters that affect or interest them. The questions that guided the study were: 1) what factors influence citizen involvement in matters that concern them in new management era in Kenya? 2) What methods are available to foster public participation in new management era in Kenya? Arnstein’s Ladder and IAP2 spectrum of citizen participation formed the theoretical framework on which the study was anchored. Analytical inquiry design was used. Data was collected by desk review using Google Scholar as search engine to access e-libraries. Thirty three sources composed of journal articles, books, conference papers and reports by government agencies and United Nations, published between 2010 and 2020 were reviewed. The critical analysis of literature revealed four sets of factors (demography, motivation, structure and environment) that influenced citizen participation. Leveraging on technology to compliment face-to-face public participation with online (e-participation), developing cooperative system between national and local government that provides structured participation such as ‘local councils’ or ‘ward committees’ are some of the methods Kenyan Government should adopt. Finally, the study suggests that the government of Kenya establishes a culture of open governance by designing and implementing policy framework that eliminated barriers to public participation.